Adaptation of the Children's automatic thoughts scale negative/positive (Cats-N/P) for Portuguese children and adolescents (Brazilian Journal of Behavioral and Cognitive Therapy, 2019)
This investigation aimed to evaluate the psychometric properties of the Portuguese adaptation of the Children's Automatic Thoughts Scale Negative/Positive (CATS-N/P) (Hogendoorn et al., 2010) and to identify age and gender differences in automatic thoughts content. Data were collected from a community sample of 330 children and adolescents, between 10 and 19 years old. The Cats/N-P revealed a five-factor structure (negative view of self, social threat, positive thoughts, physical threat and hostility) and good internal consistencies for each subscale. Results suggested divergent and convergent validity – adolescents who reported more positive thoughts also reported more satisfaction with life, while adolescents with more negative view of self-thoughts reported lower levels of satisfaction with life. There were no age group differences in automatic thought content. However, gender differences were verified, with boys reporting more positive thoughts, and girls having more thoughts regarding a negative view of themselves.
Keywords: automatic thoughts; satisfaction with life; cognitive therapy with adolescents; adolescence; Cats-N/P